#TITLE_ALTERNATIVE# - IRAWAN (NIM 12005020), INDRA
Outcrops in study area can be divided into 2 rock units: Claystone of Citarum Formation as the oldest and Sandstone-Claystone of Citarum Formation as the youngest. Sandstone-claystone of Citarum Formation consists of conglomeratic sandstone, coarse sandstone with massive sediment structure, and interbeded between fine-medium sandstone with claystone. Shallow ocean and deep ocean fossils are found in the Claystone of Citarum Formation. Sandstone in Sandstone-Claystone of Citarum Formation is wacke sandstone with Bouma sequence structure developed (Ta-Tc) so conclusion can be made that the study area are deposited by gravity flow mechanism. Rocks in study area consist lots of volcanic materials that is indicate the volcanic activity influence in deposited process at study area. Turbidite facies analysis was held to the sandstone-claystone unit in the study area where facies A, B, and C were found. Based on facies domination, writer grouped it into 4 facies association, which are: facies association I, facies association II, facies association III, and facies association IV. Based on micropaleontology analysis, there is a change in fossils amount consisted in rocks. In the lower part interval, the occurence is abundance. On the contrary, the occurence in the medium part decreased till no fossils found in the upper part. However, in the most upper part, fossils are found even in a very small amount. This shows that there was a change in the deposition rate which became faster, and the rate slowed in the most upper interval, showed by the small amount fossils found.